Potential impact of platelet-to-lymphocyte ratio on prognosis in patients with colorectal cancer: A systematic review and meta-analysis - Guo, Ganlin; Hu, Xuhua; Gao, Tianyi; Zhou, Huixian; Li, Baokun; Zhou, Chaoxi; Yu, Bin; Wang, Guiying (Frontiers in Surgery, 2023)
Background Numerous studies have confirmed that inflammation promotes the occurrence, development and prognosis of colorectal cancer (CRC). Objective This study focuses on the potentially prognostic value of the platelet-to-lymphocyte ratio (PLR) in CRC patients. Data Sources This study was registered at PROSPERO (ID: CRD42020219215). Relative studies were searched on PubMed, Cochrane Library, Embase, Web of Science, and clinical trial databases by two back-to-back reviewers. Study Selection and Intervention: Studies were screened according to the predetermined inclusion and exclusion criteria, comparing prognosis differences between low PLR levels and high PLR levels for CRC patients. Main Outcome Measures: Studies were integrated and compared to analyze the value of PLR in predicting overall survival (OS), progression-free survival (PFS), cancer-specific survival (CSS), disease-free survival (DFS) and recurrence-free survival (RFS) of CRC. Results: Outcomes were compared using Review Manager (version 5.4) software from Cochrane Collaboration. A total of 27 literary works, including 13,330 patients, were incorporated into our study. The final results showed that higher PLR levels had worse OS (hazard ratio [HR] = 1.40, 95% confidence interval [CI] = 1.21–1.62, P < 0.00001), DFS (HR = 1.44, 95% CI = 1.09–1.90, P = 0.01) and RFS (HR = 1.48, 95% CI = 1.13–1.94, P = 0.005) than lower PLR levels, respectively. However, there was no evidence of significance for PFS (HR = 1.14, 95% CI = 0.84–1.54, P = 0.40) and CSS (HR = 1.16, 95% CI = 0.88–1.53, P = 0.28) in the final meta-analysis. Limitations Our study has the following limitations. First of all, we only included literature published in English, which means that some publication bias may be inevitable. In addition, our study used aggregate data, not individual data; furthermore, we did not define the exact cut-off value representing the PLR level. Conclusion An elevated PLR seems to be an adverse prognostic factor affecting survival outcomes in patients with CRC. Meanwhile, more prospective studies are required to confirm our conclusion. PROSPERO ID: CRD42020219215.